The Novel Psychoactive Substance Cumyl-CH-MEGACLONE: Human Phase-I Metabolism, Basic Pharmacological Characterization and Comparison to Other Synthetic Cannabinoid Receptor Agonists with a γ-Carboline-1-One Core. Issue 3 (6th June 2020) - Haschimi, Belal; Giorgetti, Arianna; Mogler, Lukas; Nagy, Tibor Zsigmond; Kramer, Selina; Halter, Sebastian; Boros, Sándor; Dobos, Adrienn; Hidvégi, Előd; Auwärter, Volker
Abstract: Synthetic cannabinoids (SC) remain one of the largest groups of new psychoactive substances on the European drug market. In December 2018, Cumyl-CH-MEGACLONE, a novel SC based on a γ-carboline-1-one core structure, was firstly identified in Hungary and later also other European countries. This work aims to reveal the pharmacological characteristics and phase-I metabolism of Cumyl-CH-MEGACLONE and compare the data to its analogs Cumyl-PEGACLONE and 5F-Cumyl-PEGACLONE. The purified substance was characterized by means of gas chromatography–mass spectrometry (GC–MS), liquid chromatography–quadrupole time-of-flight mass spectrometry (LC–QToF-MS), attenuated total reflection infrared spectroscopy (ATR-FTIR) and nuclear magnetic resonance spectroscopy. Phase-I metabolites were identified by LC–QToF-MS analysis combined with a scheduled precursor ion list of authentic urine samples and confirmed by comparison with metabolites built in vitro by pooled human liver microsome assays. Pharmacological data were obtained in a competitive ligand binding assay and a receptor activation assay at the human cannabinoid receptor 1 (hCB1 ). The structure of 5-cyclohexylmethyl-2-(2-phenylpropan-2-yl)-2, 5-dihydro-1 H -pyrido[4, 3- b ]indol-1-one (semisystematic name: Cumyl-CH-MEGACLONE) was identified in a herbal blend as the main active ingredient. Investigation of phase-I biotransformation of Cumyl-CH-MEGACLONE led to three monohydroxylated metabolites (M08, M10 and M13) as reliable urinary markers for proof of consumption. At the hCB1, Cumyl-CH-MEGACLONE shows high binding affinity with K i = 1.01 nM (2.5-fold higher than JWH-018), an EC 50 of 1.22 nM and high efficacy with E MAX = 143.4% above constitutive activity of the receptor (1.13-fold higher than JWH-018). Comparison to the analogs 5F-Cumyl-PEGACLONE and Cumyl-PEGACLONE (both are hCB1 full agonists carrying a 5-fluoropentyl or pentyl chain instead of the cyclohexylmethyl moiety) suggests that Cumyl-CH-MEGACLONE is more likely to resemble the pharmacologic profile of the latter one.